MINI REVIEW RECENT ADVANCES IN LIFEPO₄ CATHODE MATERIALS FOR LITHIUM-ION BATTERIES: SYNTHESIS, CHARACTERIZATION, AND PERFORMANCE OPTIMIZATION - Vamellia Sari Indah Negara (Bajang Institute, 2024)
Lithium-ion batteries (LIBs) have revolutionized energy storage systems due to their high energy density, long cycle life, and wide range of applications. Among cathode materials, LiFePO₄ (LFP) has emerged as a promising candidate due to its excellent thermal stability, high safety, and long-term cycling performance. LFP features an olivine structure with a theoretical capacity of 170 mAh g⁻¹ and an operating voltage of approximately 3.4 V vs. Li/Li⁺, making it ideal for electric vehicles and renewable energy storage. However, its low electronic conductivity and slow lithium-ion diffusion present key challenges. Various strategies have been developed to overcome these limitations, including nanoengineering, doping, and conductive coatings. Synthesis methods such as sol-gel, solvothermal, and solid-state reactions have been employed to optimize particle structure and morphology. Characterization techniques such as X-ray diffraction (XRD), scanning electron microscopy (SEM), and X-ray absorption spectroscopy (XANES and EXAFS) provide deep insights into the structural and electrochemical properties of LFP. This study highlights recent advances in LFP materials and optimization strategies to enhance its performance for next-generation battery applications.